The effect of 1-ethyl-3-methylimidazolium acetate on the structural, morphological and electrical properties of poly (methyl methacrylate) (PMMA)-based electrolyte films / Nurul Nur Syafiqah Azriza ... [et al.] - Azriza, Nurul Nur Syafiqah; Muhd Zailani, Nabilah Akemal; Nagoor Gunny, Ahmad Anas; Nazir, Khuzaimah; Zainal, Mohamad Fetri; Abdul Latif, Famiza (Research Management Institute (RMI), 2024)
In this study, the ionic liquid (IL) of 1-ethyl-3-methylimidazolium acetate, [EMIM][Ac] was incorporated into the PMMA-based electrolyte via solution casting technique. Lithium triflate (LiTf) was also doped into the system to provide additional charge carrier. The effect of various amount [EMIM] [Ac] towards the structural, morphological, and electrical properties of PMMA-based PE films were determined using Fourier transform infrared spectroscopy (FTIR), optical microscope (OM) and electrochemical impedance spectroscopy (EIS) respectively. Solid, flexible, and free-standing films of PMMA-based electrolyte were successfully obtained after the addition of IL. As confirmed from FTIR analyses, there occurs interaction between the oxygen atoms of PMMA with the imidazolium cation of the IL. With the addition of IL, the ionic conductivity was also observed to increase which can be related to the large structure of IL that occupy the space between PMMA chain hence reduced the formation of hydrogen bonding. This has been further confirmed by the OM analyses which showed the increase in grain size for the modified PMMA system after the doping of IL. The highest conductivity of 9.86 x 10-7 S cm-1 was obtained when 42 wt.% IL (PMMAIL5) was incorporated into the PMMA-based electrolyte system. This is due to the increase in the amorphosity of the sample which improved the ion diffusion within the polymer complex. The increase in the amorphosity of the sample is confirmed by the reduced in the number of grains as observed in the optical micrograph of PMMAIL5.